Assessment of Effect of 6% Hydroxyethyl Starch Pre?Administration for Reduction of Pain on Propofol Injection - Akhila Reddy; A. Raghavendra (Academia Anesthesiologica International, 2021)
Background: The aim is to assess effect of 6% hydroxyethyl starch pre?administration for reduction of pain on propofol injection.                     Subjects and Methods: Eighty- eight adult patients were classified patients into 2 groups. Group A received 100 mL bolus of HES and group B received 0.9% normal saline (NS) over three to five minutes through an 18 G cannula placed in the hand or forearm vein, followed by induction with 1% propofol premixed with 2% lidocaine. Pain during propofol injection was assessed every 10 seconds before the loss of verbal contact. Results: Group A comprised of 24 males and 20 females and group B had 21 males and 23 females. The mean weight was 60.5 kgs in group A and 59.8kgs in group B. Propofol induction dose in group A was 126 mg and in group B was 130. Loss of verbal response was 57 seconds in group A and 58 seconds in group B. The difference was non- significant (P> 0.05). Grade 0 was seen in 62% in group A and 40% in group B, grade 1 in 20% in group A and 35% in group B, grade 2 in 13% in group A and 15% in group B and grade 3 in 5% in group A and 10% in group B. The difference was non- significant (P> 0.05).Conclusion: Pre-administration of 100 mL of 6% HES, 3 to 5 min before propofol injection, significantly decreases the pain on injection with propofol in comparison to normal saline.